Regional trade agreements and developing countries : the case of the Pacific Islands' proposed free trade agreement - Scollay, Robert (UN New YorkUS, 2001)
Focuses on a proposal to form a free trade area among the Forum Island countries. Demonstrates that the advantages and disadvantages of a given regional trade agreement proposal need to be assessed in the light of the participating countries and their trade. Notes that grasping the full implications of a proposal such as the free trade area of the Forum Island countries requires an understanding of how the proposed arrangement may interact with the members' trade relations with their major developed country economic partners.